Decision Making on The Organoleptic Quality of Salted Egg Products using Analytical Hierarchy Process and Simple Additive Weighting - Muliawati, Tri Hadiah; Yunanto, Andhik Ampuh; Pratama, Borneo Satria; Nugraha, Aditya Wahyu; Subara, Deni; Afifah, Amalia; Sariati, Sariati (LPPM Universitas Dian Nuswantoro, 2024)
Chicken and duck eggs are highly nutritious food products that are popular among the Indonesian community. However, their perishable nature leads to a decline in quality if not further processed. The salting process is a simple preservation method that can also enhance the flavor of salted egg products. To produce salted egg products with high organoleptic quality preference, a combination of Analytical Hierarchy Process (AHP) and Simple Additive Weighting (SAW) is implemented as a quality decision-making method based on: (1) the experts viewpoints on the importance level of organoleptic criteria, and (2) the scores of organoleptic tests for the criteria of texture, taste, and appearance. In this study, chicken and duck eggs were processed into salted eggs using a salting mixture made of a blend of scouring ash and table salt with a mass ratio of 5:4 and 5:6, resulting in product combinations coded as CE-5/4, CE-5/6, DE-5/4, and DE-5/6. Data processing results on the importance level from the experts viewpoints using the AHP method resulted that the criteria for texture, taste, and aroma had final priority weights of 0.244, 0.617, and 0.139, respectively. Final decision-making using the SAW method indicated that the highest to lowest final preference scores were obtained by products CE-5/4, DE-5/4, DE-5/6, and CE-5/6, with the final preference scores of 0.979, 0.963, 0.931, and 0.906, respectively. The results demonstrated that AHP and SAW were successfully implemented to assist in making decisions regarding the quality of salted egg products based on their organoleptic characteristics. Keywords: salted egg, organoleptic, decision-making, AHP, SAW